Genetski dejavniki in rak prostate (vpliv polimorfizmov C825T v genu GNB3 in D85Y v genu UGT2B15) - Hajdinjak, Tine (Zdravniški vestnik, 2004)
Background. In Slovenia, incidence of prostate cancer (CaP) is approximately half of incidence in neighbouring Austria. With ageing of population and increasing awareness, incidence is increasing. Treatment of CaP can drastically decrease quality of life and course of disease is not possible to predict. As main risk factor for CaP is heredity, one way of looking for prognostic factors is evaluation of influence of single nucleotide polymorphisms (SNPs). Methods. DNA was isolated from peripheral blood of 86 patients with histologically proven prostate cancer and 178 controls. Polymorphisms D85Y in gene UGT2B15 and C825T in gene GNB3 were evaluated with RFLP. Frequencies of alleles were compared between controls and patients and between patients stratified according to the Gleason score (less than 7 and 7 or more). Results. D85Y: patients: 23% DD, 49% DY, controls 16% DD, 52% DY (NS). In patients with Gleason score 7 or more frequency of DD was 33% and with Gleason score less than 7 15% (risk ratio for DD 2.97, p = 0.041). C825T: patients: 14% TT, 44% CT, controls 8% TT, 46% CT (NS). Conclusions. Although study did not confirm influence of evaluated polymorphisms on risk for developing prostate cancer, we identified significantly higher frequency of D allele of polymorphism D85Y in subgroup of patients with poorly differentiated CaP. This polymorphism could become one of the prognostic factors in CaP.
Keywords: diagnostika; genetics; genetika; Incidence; novotvorbe; Pojavnost; polimorfizem; Polimorfizem posameznega nukleotida; Polymorphism, single nucleotide; prostata; Prostata, novotvorbe; prostate; Prostatic neoplasms; rak (medicina); tumor